A Green Gambit: The Development of Environmental Foreign Policy in Morocco - Nicolai, Katharina (Journal of North African Studies, 2020)
The Kingdom of Morocco decisively increased trade and diplomatic interaction with countries of Western and Sub-Saharan Africa since the mid-2000s, supplementing Morocco's long-standing foreign policy orientation toward the 'West'. Under the guidance of King Mohammed VI, the country gradually sought regional political rapprochement after several decades of relative isolation. The push for regional integration is taking place across multiple policy fields and goes hand in hand with a more assertive demeanour on the stage of international diplomacy. Environmental sustainability - encompassing renewable energy production and environmental protection measures - is a policy sector on which the autocratic Moroccan regime places special emphasis. This paper traces Morocco's 'green turn', the development of environmental sustainability policy under King Mohammed VI in context of Morocco's general foreign policy realignment. It analyses Morocco's environmental engagement at the foreign policy level in terms of soft power activity and gives tentative insight on Morocco's path of becoming an influential regional player in Western and Sub-Saharan Africa.
CRIS-Team WoS Importer:2021-01-22